1988
DOI: 10.1172/jci113405
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of diabetes in BB rats by virus infection.

Abstract: BB rats serve as a model for human insulin-dependent diabetes mellitus (IDDM), since without insulin treatment, most 60-140-d-old animals die within 1 to 2 wk of developing polyuria, polydypsia, hyperglycemia, and hypoinsulinemia. Lymphoid cells accumulate in the islets of Langerhans and beta cells undergo destruction. We report that inoculation of such BB rats with lymphocytic choriomeningitis virus (Armstrong strain, clone 13) reduces over a prolonged period the incidence of IDDM, normalizes the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Additionally, in this system, increased FasL expression was observed on T cells, and Fas-FasL-mediated T-cell deletion was suggested as a mechanism for the protection from diabetes (31). Virus infection can prevent diabetes in both NOD mice and the BB rat (16,47), and it has been suggested that these infections may alter the trafficking of autoreactive T cells, since infection with lymphocytic choriomeningitis virus enhances the expression of the chemokine IFN-␥-inducible protein 10 in the lymph node draining the pancreas, and it was proposed that this would lead to recruitment of T cells away from the pancreatic islets to the lymph node, where they would undergo apoptosis (10). Th2 cells induced following infection with gastrointestinal helminths result in an upregulation in expression of the integrin ␣4␤7 which binds to the mucosal addressin MAdCAM (32).…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, in this system, increased FasL expression was observed on T cells, and Fas-FasL-mediated T-cell deletion was suggested as a mechanism for the protection from diabetes (31). Virus infection can prevent diabetes in both NOD mice and the BB rat (16,47), and it has been suggested that these infections may alter the trafficking of autoreactive T cells, since infection with lymphocytic choriomeningitis virus enhances the expression of the chemokine IFN-␥-inducible protein 10 in the lymph node draining the pancreas, and it was proposed that this would lead to recruitment of T cells away from the pancreatic islets to the lymph node, where they would undergo apoptosis (10). Th2 cells induced following infection with gastrointestinal helminths result in an upregulation in expression of the integrin ␣4␤7 which binds to the mucosal addressin MAdCAM (32).…”
Section: Discussionmentioning
confidence: 85%
“…Like the NOD mouse, however, diabetes does occur earlier and with a higher frequency in VAF vivaria than in less clean environments. Deliberate infection with lymphocytic choriomeningitis virus prevents diabetes, perhaps by deleting effector T cells (Dyrberg et al 1988), but infection with Kilham rat virus (KRV 1 ) and other viruses does not affect disease frequency or age at onset ).…”
Section: Translational Modeling Powermentioning
confidence: 99%
“…These include encephalomyocarditis (EMC) virus [41,42], mengo virus [43], reovirus [44] and retrovirus [45][46][47] in mice; Coxsackie B virus, particularly B4, in mice [48,49] and non-human primates [50]; foot-and-mouth virus in pigs and cattle [51]; rubella virus in hamsters and rabbits [52,53]; bovine viral diarrhoea-mucosal disease virus in cattle [54] and Kilham rat virus (KRV) in rats [55]. In addition to inducing diabetes, there is also some evidence that viruses such as lymphocytic choriomeningitis virus (LCMV) [56,57] and mouse hepatitis virus (MHV) [58] can protect against the development of autoimmune T1D in two spontaneously diabetic animals, the BioBreeding (BB) rat and the nonobese diabetic (NOD) mouse.…”
Section: Introductionmentioning
confidence: 99%